Higher levels of peripheral blood glucose in the acute stage of stroke increase the risk of post-stroke depression: A systematic review and meta-analysis. (November 2022) - Wang, Yiwen; Zhu, Lijun; Tan, Xiangyu; Cheng, Yanwei; Wang, Xiangyi; Fang, Shaokuan
Abstract: Background: Multiple investigations have shown that diabetes mellitus is a predictor of post-stroke depression (PSD). However, whether elevated levels of fasting plasma glucose (FPG) and hemoglobin A1c (HbA1c) are associated with an increased risk of PSD remains controversial. Methods: We comprehensively searched databases for eligible studies. Standard mean differences and 95% confidence intervals were used to examine the relationship between peripheral blood glucose levels during the acute phase of stroke and the risk of PSD. Narrative syntheses and meta-analyses were conducted when appropriate unadjusted or adjusted ORs were available. Results: A total of 21 prospective cohort studies were included in the analysis. PSD patients had significantly higher peripheral blood glucose levels than non-PSD patients (FPG: SMD, 0.28, 95% CI, 0.11–0.45, p ＜0.01, HbA1c: SMD, 0.49, 95%CI, 0.20–0.78, p ＜0.01, respectively). In the subgroup analyses by classifying the time point of depression assessment, HbA1c was more statistically significant associated with the risk of PSD than FPG. Differences in the prevalence of diabetes were not heterogeneity sources. Conclusion: Higher levels of peripheral blood glucose in the acute phase of stroke increase the risk of PSD. HbA1c might be a better biomarker for the risk of PSD than FPG. Highlights: Post-stroke depression is a common psychiatric disorder that affects the neurological recovery of patients after stroke. Particular biomarkers to predict post-stroke depression are required. Higher levels of peripheral blood glucose in the acute phase of stroke increased the risk of post-stroke depression. Fasting plasma glucose and hemoglobin A1c are both important potential predictors of post-stroke depression. HbA1c is a better predictor of the risk of post-stroke depression than FPG.